Rasch model: Quality of final semester assessment items for class x on biology subject - Bekti Isnaeni; Nani Aprilia; Much Fuad Saifuddin (Biosfer: Jurnal Pendidikan Biologi, 2022)
The Final The quality of the question item is important to know to produce more accurate measurements. Final Semester Assessment questions have not been analyzed, and many students still have not passed the Minimum Criterion of Mastery Learning (MCML). This research aims to determine the quality of the question items in the Final Semester Assessment of State High School in the Gondokusuman District. This research uses a quantitative descriptive approach. The population and sample in this study were the answer sheets of all students of class X MIPA at 6th and 9th State Senior High School Yogyakarta in the 2020/2021 school year, which amounted to 462 sheets. Sampling techniques used saturated samples. The data collection procedures were observation and documentation; The analysis was quantitative descriptive. Research results showed the results as 1) there is a difference in the level of question validity of the two schools; 2) The reliability of the questions whether by 6th and 9th State Senior High School Yogyakarta had excellent value; 3) The difficulty level of questions at SMA N 6 Yogyakarta is higher than SMA N 9 Yogyakarta; 4) Differentiating level of the questions by 6th State Senior High School Yogyakarta was seven groups of questions and the questions by 9th State Senior High School Yogyakarta was 11 groups of questions; 5) The effectiveness of distracting questions at 6th and 9th State Senior High School Yogyakarta is not practical; 6) The suitability of the questions with the material and construction aspects of the questions at SMA N 9 Yogyakarta is better than SMA N 6 Yogyakarta.